FACTORS AFFECTING HALAL SATISFACTION AND LOYALTY IN THE HOSPITALITY INDUSTRY - Candraningrat Candraningrat (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2024)
This study aims to identify and analyze the factors influencing customer satisfaction and loyalty in the Sharia hotel industry in East Java, focusing on service quality, hotel facilities, accessibility, and expectation toward service. A quantitative research method was employed, collecting data through questionnaires distributed to customers of Sharia hotels in East Java. Data analysis techniques included descriptive analysis, convergent validity testing, Average Variance Extracted (AVE), Composite Reliability, and Cronbach's Alpha to measure the reliability and validity of the data.The results indicate that service quality, hotel facilities, and accessibility have a significant positive impact on expectations toward service, which in turn significantly affects customer satisfaction and loyalty. Specifically, Sharia-compliant and easily accessible hotel facilities enhance customers' expectations regarding the services they receive. Fulfilled or exceeded expectations then increase customer satisfaction, which directly contributes to customer loyalty. This research contributes to the existing literature by providing a deeper understanding of the factors affecting customer satisfaction and loyalty in the context of Sharia hotels in East Java, and offers practical insights for hotel managers in developing effective service strategies.